Water-soluble gel electrolyte, preparation method thereof, water-based slurry and application
By preparing water-soluble gel electrolytes and applying them to lithium battery separators, the problems of poor physical and chemical performance and interface properties of the existing separator coating are solved, and higher ion transport capacity and cycling performance are achieved, and the amount of electrolyte added and internal resistance are reduced.
Patent Information
- Application Number
- CN202411478492.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-02-25
AI Technical Summary
The existing lithium battery separator coatings have problems with poor physical and chemical properties and interface properties.
A method for preparing water-soluble gel electrolyte is adopted to polymerize methyl methacrylate and N-isopropyl acrylamide, combined with neopentyl glycol diglycidyl ether, and the water-soluble gel electrolyte is obtained after heating treatment and sieving, and it is applied to the battery separator as an aqueous slurry.
It improves the ion transmission capability of the battery separator, reduces internal resistance, enhances cycling performance, reduces the amount of electrolyte added, and improves the safety performance and breathability of the battery cell.
Smart Images

Figure BDA0005096713020000101 
Figure BDA0005096713020000111 
Figure BDA0005096713020000141
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium battery separators, and in particular to a water-soluble gel electrolyte and a preparation method thereof, an aqueous slurry and applications thereof. Background Art
[0002] Lithium batteries have the characteristics of high energy density, long service life, and relatively good environmental friendliness. They are widely used in energy storage systems, portable electronic products, and electric vehicles. Lithium batteries are usually classified as energy-type devices. In order to meet the needs of energy storage devices for high safety and high energy density, lithium batteries need to be continuously developed and technologically iterated. Solid-state batteries have become the first choice for development. It is crucial that the surface of the solid electrolyte diaphragm is free of pores and cracks. The diaphragm needs to have a certain inhibitory effect on the formation of lithium dendrites, so that lithium metal has chemical stability and forms a stable SEI film, and the diaphragm needs to have sufficiently high ionic conductivity. The quality and performance of the diaphragm will directly affect the energy density, safety, rate performance, and low-temperature performance of the battery; the development of high-strength, good toughness, high ionic conductivity, and flexible solid electrolyte diaphragms is the goal that researchers have been committed to researching and developing.
[0003] CN 112201845A discloses a composite diaphragm for a semi-solid electrolyte battery with an ultra-stable interface, wherein the composite diaphragm comprises a base film and a coating, wherein the coating is a solid electrolyte coating, and wherein the coating comprises an inorganic solid electrolyte, a dispersant, a thickener, a binder, a wetting agent and water. This technical solution realizes an ultra-stable interface of the battery, but the interface contact between the composite diaphragm and the pole piece is relatively poor during use.
[0004] CN 117895069A discloses a method for preparing a gel polymer electrolyte material. The method uses a precursor solution containing methyl methacrylate, N-isopropylacrylamide and neopentyl glycol diglycidyl ether to mix, and the obtained intermediate is heated twice in sequence, and the temperature of the two heating treatments is controlled. The obtained gel polymer electrolyte material improves the safety of traditional liquid batteries. However, when the electrolyte material is applied to a diaphragm, it is not heat-resistant and the ion transmission capacity and cycle performance in the battery core need to be improved. Summary of the invention
[0005] The purpose of the present invention is to overcome the problems of poor physical and chemical properties and interface properties of the diaphragm coating in the prior art.
[0006] In order to achieve the above object, the first aspect of the present invention provides a method for preparing a water-soluble gel electrolyte, the method comprising:
[0007] (1) in the presence of an initiator, subjecting methyl methacrylate and N-isopropylacrylamide to a first polymerization reaction to obtain an intermediate I;
[0008] (2) subjecting polymer solution A and polymer solution B to a second polymerization reaction to obtain intermediate ⅠⅠ; the polymer solution A contains intermediate Ⅰ at a concentration of 8-12 wt %; the polymer solution B contains neopentyl glycol diglycidyl ether at a concentration of 0.5-1.2 wt %;
[0009] (3) heating the intermediate ⅠⅠ to obtain the water-soluble gel electrolyte;
[0010] Wherein, in step (1), the conditions of the first polymerization reaction include: a rotation speed of 400-1600 rpm, a temperature of 20-45° C., and a time of 3-7 h;
[0011] In step (2), the weight ratio of the polymer solution A to the polymer solution B is 4-12:1.
[0012] The second aspect of the present invention provides a water-soluble gel electrolyte prepared by the method described in the first aspect.
[0013] A third aspect of the present invention provides an aqueous slurry, the aqueous slurry containing a water-soluble gel electrolyte, a solid electrolyte, a binder, a dispersant and water;
[0014] Wherein, the water-soluble gel electrolyte is the water-soluble gel electrolyte described in the second aspect.
[0015] The fourth aspect of the present invention provides use of the aqueous slurry described in the third aspect in a battery separator.
[0016] Through the above technical solution, the present invention has at least the following advantages:
[0017] The present invention provides a method for preparing a water-soluble gel electrolyte. When the obtained water-soluble gel electrolyte is applied to a battery separator as an aqueous slurry, the amount of electrolyte added during injection into a battery cell can be reduced, thereby effectively reducing costs. The separator coating absorbs the electrolyte, thereby reducing battery leakage and improving the safety performance of the battery cell. The separator has a strong ion transmission capability in the battery cell, thereby reducing internal resistance and effectively improving the cycle performance of the battery cell. DETAILED DESCRIPTION
[0018] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0019] In the present invention, the normal temperature refers to a temperature of 25±2°C.
[0020] It should be noted that in the present invention, the solid electrolyte and the water-soluble gel electrolyte obtained after screening exist in the form of primary particles and secondary particles after agglomeration; the average particle diameter of the solid electrolyte and the water-soluble gel electrolyte refers to the average particle diameter of a single particle.
[0021] As mentioned above, the first aspect of the present invention provides a method for preparing a water-soluble gel electrolyte, the method comprising:
[0022] (1) in the presence of an initiator, subjecting methyl methacrylate and N-isopropylacrylamide to a first polymerization reaction to obtain an intermediate I;
[0023] (2) subjecting polymer solution A and polymer solution B to a second polymerization reaction to obtain intermediate ⅠⅠ; the polymer solution A contains intermediate Ⅰ at a concentration of 8-12 wt %; the polymer solution B contains neopentyl glycol diglycidyl ether at a concentration of 0.5-1.2 wt %;
[0024] (3) heating the intermediate ⅠⅠ to obtain the water-soluble gel electrolyte;
[0025] Wherein, in step (1), the conditions of the first polymerization reaction include: a rotation speed of 400-1600 rpm, a temperature of 20-45° C., and a time of 3-7 h;
[0026] In step (2), the weight ratio of the polymer solution A to the polymer solution B is 4-12:1.
[0027] Preferably, in step (1), the initiator is selected from at least one of azobisisobutyronitrile (AIBN), ammonium persulfate, benzoyl peroxide, diisopropyl peroxydicarbonate and dibenzoyl peroxide (BPO).
[0028] Preferably, in step (1), in the first polymerization reaction, the concentration of the initiator is 50-90 g / L.
[0029] Preferably, in step (1), the weight ratio of the methyl methacrylate to the N-isopropylacrylamide is 1.2-1.5: 1. In this preferred embodiment, the obtained battery separator has stronger adhesion performance when the air permeability is similar.
[0030] Preferably, in step (2), the conditions of the second polymerization reaction include: a rotation speed of 800-1400 rpm, a temperature of 20-45° C., and a time of 2-4 hours. In this preferred case, the obtained polymerization conversion rate (reaction rate) is higher, which can further reduce the cost of preparing the battery separator.
[0031] Preferably, in step (3), the conditions of the heating treatment include: a rotation speed of 800-1000 rpm, a temperature of 18-35° C., and a time of 2-4 h.
[0032] According to a preferred specific embodiment, the method further comprises: screening the product obtained by the heating treatment I to obtain the water-soluble gel electrolyte; the screening I is through a 200-300 mesh Chinese sieve.
[0033] As mentioned above, the second aspect of the present invention provides a water-soluble gel electrolyte prepared by the method described in the first aspect.
[0034] Preferably, the average particle diameter of the water-soluble gel electrolyte is 0.3-0.8 μm.
[0035] Preferably, the water-soluble gel electrolyte has a solid content of 20-40 wt % at 25°C.
[0036] As mentioned above, the third aspect of the present invention provides an aqueous slurry, which contains a water-soluble gel electrolyte, a solid electrolyte, a binder, a dispersant and water;
[0037] Wherein, the water-soluble gel electrolyte is the water-soluble gel electrolyte described in the second aspect.
[0038] Preferably, based on the total weight of the aqueous slurry, the content of the water-soluble gel electrolyte is 3-10wt%, the content of the solid electrolyte is 15-40wt%, the content of the binder is 1-5wt%, the content of the dispersant is 0.5-3wt%, and the content of water is 70-80wt%. In this preferred case, the air permeability of the obtained battery separator is better.
[0039] Preferably, the solid electrolyte is a lithium aluminum titanium phosphate solid electrolyte and / or a zirconium oxide solid electrolyte.
[0040] The present invention has no particular restriction on the sources of the lithium titanium aluminum phosphate solid electrolyte and the zirconium oxide solid electrolyte. They can be obtained by commercial purchase or self-preparation. Those skilled in the art can choose according to needs, as long as a solid electrolyte that meets the requirements of the present invention can be prepared. However, in order to obtain a battery separator with higher battery cell safety performance and better cycle performance, the present invention preferably adopts the following two methods to prepare the lithium titanium aluminum phosphate solid electrolyte and the zirconium oxide solid electrolyte respectively.
[0041] According to a preferred specific embodiment, the lithium aluminum titanium phosphate solid electrolyte is prepared by a method comprising the following steps:
[0042] S1: Combine CH3COOLi·2H2O, Al(NO3)3·9H2O, C 16 H 36 A mixture of O4Ti and NH4H2PO4 is ball-milled with ethanol to obtain a slurry;
[0043] S2: The slurry is heated I and calcined in sequence to obtain the lithium aluminum titanium phosphate solid electrolyte.
[0044] Preferably, in the mixture, the CH3COOLi·2H2O calculated as Li element, the Al(NO3)3·9H2O calculated as Al element, the C 16 H 36 The molar ratio of the content of O4Ti and the NH4H2PO4 calculated as P element is 1:0.15-0.25:1-1.5:2-2.5.
[0045] Preferably, the weight ratio of the mixture to the ethanol is 1:1-2.
[0046] Preferably, in step S1, the ball milling time is 2-5 hours.
[0047] Preferably, in step S2, the heating I includes a first heating I and a second heating I performed sequentially; wherein the conditions of the first heating I include: a temperature of 70-90°C and a time of 8-11 hours; the conditions of the second heating I include: a temperature of 280-320°C and a time of 2-5 hours.
[0048] Preferably, in step S2, the calcination conditions include: temperature of 700-1000°C and time of 4-6h.
[0049] Preferably, the method further comprises: screening the lithium aluminum titanium phosphate solid electrolyte Ⅱ; the screening Ⅱ is screening through a 200-mesh Chinese sieve and taking the sieve.
[0050] According to a preferred embodiment, the zirconium oxide solid electrolyte is prepared by a method comprising the following steps:
[0051] K1: In the presence of a precipitant and a pH adjuster, a ZrOCl2 solution is contacted and mixed with an ammonium salt solution containing a surfactant to obtain zirconium hydroxide;
[0052] K2: Sintering the zirconium hydroxide to obtain the zirconium oxide solid electrolyte.
[0053] Preferably, in step K1, the precipitant is aqueous ammonia with a concentration of 22 wt%.
[0054] Preferably, in step K1, the pH adjuster is at least one of NaOH, NaHCO3 and ammonia water, and the amount of the pH adjuster added is such that the initial pH value of the system is 7-9.
[0055] Preferably, in step K1, the surfactant is polyethylene glycol, more preferably polyethylene glycol having a number average molecular weight of 500-7000.
[0056] Preferably, in step K1, the contact mixing conditions include: temperature of 18-30° C. and time of 2-4 h.
[0057] Preferably, in step K1, the method further comprises: sequentially subjecting the zirconium hydroxide sol obtained by the contact mixing to solid-liquid separation and washing to obtain the zirconium hydroxide.
[0058] More preferably, the solid-liquid separation method is suction filtration.
[0059] More preferably, the solvent for the cleaning treatment is anhydrous ethanol.
[0060] Preferably, in step K2, the sintering conditions include: a temperature of 500-700° C. and a time of 1-3 h.
[0061] Preferably, the method further comprises: screening the zirconium oxide solid electrolyte Ⅲ; the screening Ⅲ is through a 150-300 mesh Chinese sieve.
[0062] Preferably, the average particle diameter of the solid electrolyte is 0.1-1.1 μm.
[0063] Preferably, the weight ratio of the water-soluble gel electrolyte to the solid electrolyte is 1:4-8.
[0064] Preferably, the adhesive is selected from at least one of polyvinylidene fluoride, sodium carboxymethyl cellulose and polyacrylic acid.
[0065] Preferably, the adhesive is polyvinylidene fluoride (PVDF), and the grade of the polyvinylidene fluoride (PVDF) is preferably PVDF 5130 and / or PVDF 900.
[0066] Preferably, the adhesive has a D 50 <1.0μm.
[0067] Preferably, the weight average molecular weight of the adhesive is 150,000-600,000.
[0068] It should be noted that D 50 It refers to the particle size corresponding to 50% of the cumulative particle size distribution of the adhesive measured by Mastersizer 3000 laser particle size analyzer, that is, the particles with a particle size less than or equal to (≤) this particle size account for 50%.
[0069] Preferably, the adhesive has a viscosity of 7300-9300 centipoise at 25° C. and a solid content of 10-20 wt %.
[0070] Preferably, the dispersant is selected from at least one of dispersant KD-1, polyethylene, polypropylene, polystyrene, unsaturated polyaminoamide and acidic polyester copolymer; wherein the dispersant KD-1 is a cationic polymer.
[0071] Preferably, the weight average molecular weight of the dispersant is 250,000-600,000.
[0072] Preferably, the density of the dispersant is 1-2 g / mL; the solid content at 25° C. is >80 wt %, and the viscosity is 100-1000 mPa·s.
[0073] As mentioned above, the fourth aspect of the present invention provides the use of the aqueous slurry described in the third aspect in a battery separator.
[0074] Preferably, the application method comprises:
[0075] (T1) pretreating the aqueous slurry in the presence of water to obtain product A;
[0076] (T2) coating the product A on a base film to obtain a battery separator.
[0077] The aqueous slurry is the aqueous slurry described in the third aspect, which will not be described in detail here.
[0078] More preferably, the pretreatment comprises stirring, defoaming, sieving IV and filtering in sequence; the sieving IV is through a 200-300 mesh Chinese sieve.
[0079] Further preferably, the stirring conditions include: a rotation speed of 300-1500 rpm, a temperature of 18-30° C., and a time of 1-3 h.
[0080] According to a preferred embodiment, the defoaming method is ultrasonic vibration and standing.
[0081] Preferably, the defoaming time is 2-5h.
[0082] The present invention has no special requirements for the coating method. For example, the coating can be performed by rolling or spraying.
[0083] Preferably, the coating conditions include: a rotation speed of 4200-5800 rpm and a flow rate of 200-800 mL / min.
[0084] Preferably, the average surface density of the coating is 0.6-2 g / cm 2 .
[0085] Preferably, the base film is a PE base film.
[0086] The present invention will be described in detail below by way of examples. In the following examples, unless otherwise specified, the compounds and reagents used are all commercially available.
[0087] Polyethylene glycol, purchased from Aladdin, CAS No.: 25322-68-3, number average molecular weight: 6000.
[0088] Lithium aluminum titanium phosphate solid electrolyte, with an average particle diameter of 0.6μm.
[0089] Zirconia solid electrolyte, average particle diameter is 0.5μm.
[0090] Polyacrylic acid, D 50 <1.0 μm; viscosity at 25°C is 9000 centipoise, and solid content at 25°C is 15 wt%.
[0091] Unsaturated polyaminoamide and acidic polyester copolymer, density is 1.08g / mL; solid content at 25°C is>90wt%, viscosity is 500-800mpa·s.
[0092] The base film is a PE base film.
[0093] In the following examples, the average particle diameters of the solid electrolyte and the water-soluble gel electrolyte were measured by a Malvern nano-laser particle size analyzer ZEN3690.
[0094] In the following examples, 1 wt% represents 100 g; the solid content refers to the value obtained by testing at 25°C.
[0095] Preparation Example 1-1: Preparation of lithium aluminum titanium phosphate solid electrolyte
[0096] (1) Combine CH3COOLi·2H2O, Al(NO3)3·9H2O, C 16 H 36 A mixture of O4Ti and NH4H2PO4 and anhydrous ethanol were placed in a ball mill and ball-milled for 4 h to obtain a slurry;
[0097] Among them, CH3COOLi·2H2O calculated by Li element, Al(NO3)3·9H2O calculated by Al element, C 16 H 36 The molar ratio of O4Ti and NH4H2PO4 calculated as P element is 1:0.23:1.3:2.3;
[0098] The weight ratio of the mixture to anhydrous ethanol is 1:1-2.
[0099] (2) The slurry is subjected to a first heating step I (temperature of 80°C for 10 h) and then ground and placed in an alumina crucible, and subjected to a second heating step II (temperature of 300°C for 3 h) and calcination (temperature of 900°C for 5 h), and then sieved I I (through a 200-mesh Chinese sieve and taking the material on the sieve) to obtain a lithium aluminum titanium phosphate solid electrolyte.
[0100] Preparation Example 1-2: Preparation of zirconium oxide solid electrolyte
[0101] (1) In the presence of a precipitant (22 wt% ammonia water) and a pH adjuster (NaHCO3), a ZrOCl2 solution was contacted and mixed with an ammonium salt solution containing a surfactant (polyethylene glycol) (temperature 20°C, time 3 h);
[0102] The obtained zirconium hydroxide sol is then filtered by suction to separate the solid from the liquid, and washed with anhydrous ethanol to obtain zirconium hydroxide;
[0103] The amount of the pH regulator added is such that the initial pH value of the system is 9 and remains constant.
[0104] (2) The zirconium hydroxide is sintered (temperature is 600° C., time is 2 h), and then sieved IIIII (through a 200-mesh sieve) to obtain a zirconium oxide solid electrolyte.
[0105] Preparation Example 2-1: Preparation of water-soluble gel electrolyte
[0106] (1) in the presence of an initiator (azobisisobutyronitrile at a concentration of 70 g / L), methyl methacrylate and N-isopropylacrylamide are subjected to a first polymerization reaction to obtain an intermediate I;
[0107] (2) subjecting polymer solution A and polymer solution B to a second polymerization reaction to obtain intermediate ⅠⅠ; polymer solution A contains intermediate Ⅰ; polymer solution B contains neopentyl glycol diglycidyl ether;
[0108] (3) The intermediate Ⅱ is subjected to a heat treatment and then sieved Ⅰ (through a 200-300 mesh Chinese sieve) to obtain a water-soluble gel electrolyte.
[0109] The raw material ratio and process conditions of this preparation example are shown in Table 1.
[0110] The methods for preparing water-soluble gel electrolytes used in the examples of the present invention are the same, except that the raw material ratios and process conditions are different, and water-soluble gel electrolytes with different characteristic parameters are obtained respectively. The raw material ratios and process conditions of the water-soluble gel electrolytes are listed in Table 1, and the unlisted parts are the same as those in Preparation Example 2-1.
[0111] Table 1 (the amount of methyl methacrylate is 100g)
[0112]
[0113]
[0114] Example 1: Application of aqueous slurry in battery separator
[0115] The methods of application include:
[0116] (1) In the presence of deionized water, the aqueous slurry was stirred at 400 rpm for 2 h at 25° C., subjected to defoaming treatment by ultrasonic vibration and standing for 3 h, passed through a 200-300 mesh sieve, and poured into a sprayer for filtration to obtain product A;
[0117] The aqueous slurry contains a binder (polyacrylic acid), a dispersant (unsaturated polyaminoamide and acidic polyester copolymer), water, and the aforementioned solid electrolyte and the water-soluble gel electrolyte prepared in Preparation Example 2-1.
[0118] (2) Set the coating machine to appropriate parameters (rotation speed of 5000 rpm, flow rate of 500 mL / min), and apply product A (roll coating) (coating surface density of 1.2 g / cm 2 ) on the PE base film, and after drying, the battery separator is cut into rolls.
[0119] The specific materials and reaction conditions of this example are shown in Table 2.
[0120] The remaining examples were prepared using the same preparation method as Example 1, except that the materials and reaction conditions were different, as shown in Table 2.
[0121] Table 2
[0122] Example 1 Example 2 Example 3 Water-soluble gel electrolyte type Z1 Z2 Z3 Dosage / wt% 10 5 3 Solid electrolyte type Lithium Aluminum Titanium Phosphate Solid Electrolyte Zirconia solid electrolyte Lithium Aluminum Titanium Phosphate Solid Electrolyte Dosage / wt% 40 30 24 Adhesive Dosage / wt% 5 2 1 Dispersants Dosage / wt% 0.5 2 3 water Dosage / wt% 70 75 80
[0123] Example 4
[0124] A method similar to that of Example 1 is used, except that the water-soluble gel electrolyte Z1 in Example 1 is replaced by Z4 of equal mass, and the rest are the same.
[0125] Example 5
[0126] A method similar to that of Example 1 is used, except that the Ti—O—Zr composite oxide Z1 in Example 1 is replaced by Z5 of equal mass, and the rest are the same.
[0127] Example 6
[0128] According to a method similar to Example 1, the difference is that the composition of the aqueous slurry is different. The composition of the aqueous slurry is specifically:
[0129] Based on the total weight of the aqueous slurry, the content of the water-soluble gel electrolyte is 12wt%, the content of the solid electrolyte is 45wt%, the content of the binder is 6wt%, the content of the dispersant is 4wt%, and the content of water is 33wt%.
[0130] Comparative Example 1
[0131] A method similar to that of Example 1 is used, except that the water-soluble gel electrolyte Z1 in Example 1 is replaced by DZ1 of equal mass, and the rest are the same.
[0132] Comparative Example 2
[0133] A method similar to that of Example 1 is used, except that the water-soluble gel electrolyte Z1 in Example 1 is replaced by DZ2 of equal mass, and the rest are the same.
[0134] Test Case
[0135] The physical and chemical properties of the battery separator obtained in the test example include surface density, needle puncture strength, shrinkage, tensile strength, elongation, air permeability, peel strength and liquid absorption rate. The test results are shown in Table 3.
[0136] The battery separator obtained in the example is assembled into a battery cell with the positive electrode and the negative electrode through a lamination process, and the amount of electrolyte added when the battery cell is injected is recorded. At the same time, the cycle performance of the battery cell is tested, including the low-temperature double charge capacity retention rate, the room temperature cycle capacity retention rate and the high temperature cycle capacity retention rate. The test results are shown in Table 4.
[0137] The test methods involved are as follows:
[0138] (1) Surface density: obtained by sampling a certain area of the diaphragm and calculating the mass / area ratio.
[0139] (2) Shrinkage rate: The sample was placed between two 8-mm-thick glass plates and placed in an oven at 130°C and 105°C, respectively, for 1 h. The sample was taken out and the shrinkage rate was measured and calculated.
[0140] (3) Air permeability: At room temperature and 1.21 kPa pressure, 100 mL of air passes through an area of 6.45 cm 2 The time taken for the diaphragm.
[0141] (4) Liquid absorption rate: ① Cut 3 pieces of 10 cm × 10 cm diaphragm samples and place them in a glove box or -30°C dew point room for 24 h; ② Weigh and record the mass M1 of the diaphragm sample before immersion in the electrolyte, then completely immerse the diaphragm in the electrolyte and place it in a 28°C (oven) environment for 48 h;
[0142] ③ After immersion, weigh (glove box) the mass M2 of the diaphragm sample. The weighing method is: unfold the diaphragm in the electrolyte, hold one corner with tweezers and suspend it in the air for 60 seconds, then weigh it, and record the mass M2;
[0143] ④ According to the formula: liquid absorption rate = (M2-M1) / M1×100%, the liquid absorption rate is calculated.
[0144] (5) Needle puncture strength, tensile strength, elongation and peel strength: measured by loading different fixtures on a tensile testing machine;
[0145] Among them, the needle diameter is 1.0mm, the puncture rate is 250mm / min, and the puncture strength is calculated based on the puncture force; the tensile strength is measured at a tensile rate of 250mm / min, the clamp distance is 100mm, and the tensile strength and elongation are calculated based on the tensile force; the peel strength refers to peeling at 180°, at a peeling speed of 150mm / min, and the peel strength is calculated based on the peeling force.
[0146] (6) Cycle performance: The CT3001A blue-electric test system was used to test the battery at low temperature (-5°C), room temperature, and high temperature (45°C). The charge and discharge range was 2.0 to 3.65 V, and the cycle performance was obtained by step cycle testing.
[0147] Table 3
[0148]
[0149]
[0150] Table 4
[0151] Low temperature double charge capacity retention rate Normal temperature cycle capacity retention rate High temperature cycle capacity retention rate unit % % % Example 1 77.9 97.5 96 Example 2 77 97 96.2 Example 3 70 97.3 96.3 Example 4 50 96.8 95 Example 5 55 95 95.2 Example 6 39 96 96 Comparative Example 1 42 96.3 95 Comparative Example 2 37 95 95
[0152] It can be seen from the above results that the method for preparing a water-soluble gel electrolyte provided by the present invention, the prepared water-soluble gel electrolyte is applied to a battery separator as an aqueous slurry, and has better air permeability, higher peel strength and liquid absorption rate than other separators. After being assembled into a battery cell, it can improve the low-temperature double-charge capacity retention rate and the normal temperature and high-temperature cycle capacity retention rate of the battery cell.
[0153] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for preparing a water-soluble gel electrolyte, characterized in that: The method includes: (1) in the presence of an initiator, subjecting methyl methacrylate and N-isopropylacrylamide to a first polymerization reaction to obtain an intermediate I; (2) subjecting polymer solution A and polymer solution B to a second polymerization reaction to obtain intermediate ⅠⅠ; the polymer solution A contains intermediate Ⅰ at a concentration of 8-12 wt %; the polymer solution B contains neopentyl glycol diglycidyl ether at a concentration of 0.5-1.2 wt %; (3) heating the intermediate ⅠⅠ to obtain the water-soluble gel electrolyte; Wherein, in step (1), the conditions of the first polymerization reaction include: a rotation speed of 400-1600 rpm, a temperature of 20-45° C., and a time of 3-7 h; In step (2), the weight ratio of the polymer solution A to the polymer solution B is 4-12:
1.
2. The method according to claim 1, wherein: In step (1), the weight ratio of the methyl methacrylate to the N-isopropylacrylamide is 1.2-1.5:
1.
3. The method according to claim 1 or 2, wherein: In step (2), the conditions of the second polymerization reaction include: a rotation speed of 800-1400 rpm, a temperature of 20-45° C., and a time of 2-4 h; And / or, in step (3), the conditions of the heating treatment include: a rotation speed of 800-1000 rpm, a temperature of 18-35° C., and a time of 2-4 h.
4. A water-soluble gel electrolyte prepared by the method according to any one of claims 1 to 3.
5. The water-soluble gel electrolyte according to claim 4, wherein The average particle diameter of the water-soluble gel electrolyte is 0.3-0.8 μm; And / or, the water-soluble gel electrolyte has a solid content of 20-40 wt % at 25° C.
6. An aqueous slurry, characterized in that The aqueous slurry contains a water-soluble gel electrolyte, a solid electrolyte, a binder, a dispersant and water; Wherein, the water-soluble gel electrolyte is the water-soluble gel electrolyte according to claim 4 or 5.
7. The aqueous slurry according to claim 6, wherein Based on the total weight of the aqueous slurry, the content of the water-soluble gel electrolyte is 3-10wt%, the content of the solid electrolyte is 15-40wt%, the content of the binder is 1-5wt%, the content of the dispersant is 0.5-3wt%, and the content of water is 70-80wt%.
8. The aqueous slurry according to claim 6 or 7, wherein The solid electrolyte is a lithium aluminum titanium phosphate solid electrolyte and / or a zirconium oxide solid electrolyte; and / or, the average particle diameter of the solid electrolyte is 0.1-1.1 μm; And / or, the weight ratio of the water-soluble gel electrolyte to the solid electrolyte is 1:4-8.
9. The aqueous slurry according to any one of claims 6 to 8, wherein: The adhesive is selected from at least one of polyvinylidene fluoride, sodium carboxymethyl cellulose and polyacrylic acid; and / or, the adhesive has a viscosity of 7300-9300 centipoise at 25° C. and a solid content of 10-20 wt %; And / or, the dispersant is selected from at least one of dispersant KD-1, polyethylene, polypropylene, polystyrene, unsaturated polyaminoamide and acidic polyester copolymer; wherein the dispersant KD-1 is a cationic polymer; And / or, the density of the dispersant is 1-2 g / mL; the solid content at 25° C. is >80 wt %, and the viscosity is 100-1000 mPa·s.
10. Use of the aqueous slurry according to any one of claims 6 to 9 in battery separators.
Citation Information
Patent Citations
Ultra-stable interface semi-solid electrolyte battery composite diaphragm and preparation process thereof
CN112201845A
Gel polymer electrolyte material and preparation method and application thereof
CN117895069A
Cited By
Composite diaphragm, preparation method thereof and lithium ion battery
CN119994396A
Slurry for preparing electrode, silicon negative electrode, and solid-state battery
CN121769019A
Slurry for electrode preparation, silicon negative electrode, and solid-state battery
CN121769019B